PENGARUH KEJELASAN SASARAN ANGGARAN, KOMITMEN ORGANISASI, DAN PENGENDALIAN AKUNTANSI TERHADAP KINERJA MANAJERIAL (Studi pada SKPD Kabupaten Aceh Tamiang) - Yogi Mahestu; Nurlina; muhammad Salman; Rahmad Tantawi (Program Studi Akuntansi, Fakultas Ekonomi. Universitas Samudra, 2023)
This study aims to determine the effect of Clarity of Budget Targets, Organizational Commitment, and Accounting Control on Managerial Performance. This research was conducted at the SKPD of Aceh Tamiang Regency. The sample in this study amounted to 84 people. The sampling technique used purposive sampling, namely sampling using certain criteria. This research is a quantitative research in the form of data in the form of numbers. The data source used is primary data. Data obtained from distributing questionnaires to research respondents. The data analysis technique used multiple regression analysis assisted by the SPSS program. The results of the study partially show that Clarity of Budget Targets, Organizational Commitment, and Accounting Control have a significant effect on on Managerial Performance in the SKPD Aceh Tamiang. Simultaneous Clarity of Budget Targets, Organizational Commitment, and Accounting Control on Managerial Performance in the SKPD Aceh Tamiang. The limitation of this research is that the sample is only taken from the parties participating in this study is that in collecting data, researchers only use the questionnaire method, so they will not get answer that better reflect the actual situation. Suggestions for future researchers to expand this research by adding other variables and it is hoped that this can be done with other methods to obtain complete data, for example by conducting direct interviews with respondents in flling out the questionnaire so that the respondents answer better reflect the actual answer.